Exploring Skin Biometrics, Sensory Profiles, and Rheology of Two Photoprotective Formulations with Natural Extracts: A Commercial Product Versus a Vegan Test Formulation - Karine Campos Nunes; Bruna Lendzion Alves; Rafaela Said dos Santos; Lennon Alonso de Araújo; Rosângela Bergamasco; Marcos Luciano Bruschi; Tânia Ueda-Nakamura; Sueli de Oliveira Silva Lautenschlager; Celso Vataru Nakamura (Cosmetics, 2025)
Cumulative exposure to UV radiation can lead to harmful effects such as skin burns, photoaging, and skin cancer, thus highlighting the importance of using photoprotective formulations. Many sunscreens are vegan and have antioxidant substances to ensure additional photochemoprotective action. We evaluated biophysical, rheological, and sensorial parameters of Face Care Facial Moisturizing Cream® (P1) and a vegan formulation (P2) by in vitro and in vivo tests. Sun Protection Factor (SPF) was evaluated by Mansur method. Biophysical parameters were analyzed: sebum content, hydration level, transepidermal water loss, erythema and melanin level, skin color, and skin pH. The acceptance profile of the formulations was determined using a 9-point hedonic scale and a 5-point purchase intention test. The SPF values of P1 and P2 obtained by in vitro tests were 25.21 and 12.10, respectively. They also exhibited pseudoplastic and thixotropic behavior, which could contribute to better spreadability and form a protective film. Biometric tests showed an increase in hydration and skin sebum, decreased erythema, and maintenance of skin pH after application of both formulations. The comparison of a commercialized product and a vegan test version showed similar rheological and great acceptance profiles. Therefore, the vegan formulation is a good alternative to reach a different market.